Availability and Use of Assistive Technology for Learning Amongst Special Students in Kwara State School for Special Needs - Charles Olabode Olumorin; Ebenezer Omolafe Babalola; Barakat Kanyinsola Amoo (Indonesian Journal of Community and Special Needs Education, 2022)
Assistive Technology (AT) is a technology used by individuals with disabilities to perform functions that might otherwise be difficult or impossible. ATs are integrated into teaching and learning procedures to overcome the challenges faced by students with disabilities in educational institutions. The population of this study consisted of all the special students in Ilorin, Kwara State School for special needs. A random sampling technique was employed to select 100 students who constitute the sample size of this study. The findings of the study showed that deaf, blind, physical disability, learning disability, and language disorder are being catered for in the school,  assistive technologies are available for all the special students in the school, majority of the students used the assistive technologies for learning, there is a significant difference in the level of utilization of assistive technologies for learning among the special students based on gender, and there is a significant difference in the level of utilization of assistive technologies for learning among special students based on age. This study concluded that basic disabilities are being catered for in the sample special school with appropriate assistive technologies, and the technologies are found to be adequately available for the students. The study, therefore, recommended that the ministry of education should put in place, seminars, workshops, conferences, and training for special education teachers.